Nicorandil prevents sirolimus-induced production of reactive oxygen species, endothelial dysfunction, and thrombus formation - Ken Aizawa; Youko Takahari; Naoko Higashijima; Kenichi Serizawa; Kenji Yogo; Nobuhiko Ishizuka; Koichi Endo; Naoto Fukuyama; Katsuya Hirano; Hideyuki Ishida (Elsevier, 2015)
Sirolimus (SRL) is widely used to prevent restenosis after percutaneous coronary intervention. However, its beneficial effect is hampered by complications of thrombosis. Several studies imply that reactive oxygen species (ROS) play a critical role in endothelial dysfunction and thrombus formation. The present study investigated the protective effect of nicorandil (NIC), an anti-angina agent, on SRL-associated thrombosis. In human coronary artery endothelial cells (HCAECs), SRL stimulated ROS production, which was prevented by co-treatment with NIC. The preventive effect of NIC on ROS was abolished by 5-hydroxydecanoate but not by 1H-[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one. NIC also inhibited SRL-induced up-regulation of NADPH oxidase subunit p22phox mRNA. Co-treatment with NIC and SRL significantly up-regulated superoxide dismutase 2. NIC treatment significantly improved SRL-induced decrease in viability of HCAECs. The functional relevance of the preventive effects of NIC on SRL-induced ROS production and impairment of endothelial viability was investigated in a mouse model of thrombosis. Pretreatment with NIC inhibited the SRL-induced acceleration of FeCl3-initiated thrombus formation and ROS production in the testicular arteries of mice. In conclusion, NIC prevented SRL-induced thrombus formation, presumably due to the reduction of ROS and to endothelial protection. The therapeutic efficacy of NIC could represent an additional option in the prevention of SRL-related thrombosis.